Environment-friendly material for meal boxes and preparation process thereof
By preparing lignin-based epoxy resin through reduction catalytic fractionation and deep epoxidation technology, and combining it with surface pretreatment and silane coupling agents, the safety and performance issues of starch-based lunch boxes have been solved, achieving the preparation of high-performance environmentally friendly lunch boxes that meet food safety and environmental protection requirements.
Patent Information
- Application Number
- CN202610754721.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-28
- Publication Date
- 2026-07-03
AI Technical Summary
Existing starch-based food containers suffer from safety issues due to the use of PFAS oil-resistant agents, formaldehyde-based adhesives, and BPA raw materials, as well as problems such as low hydroxyl conversion rate, insufficient crosslinking density, high film brittleness, and poor resistance to media in traditional lignin-based epoxy resins.
High-hydroxyl-content lignin oligomers were prepared using reduction catalytic fractionation technology. Lignin-based epoxy resins were prepared through two-step deep epoxidation modification. Surface pretreatment and silane coupling agents were combined to enhance interfacial adhesion. A low-temperature curing process was then used to form a barrier coating and interlayer adhesive.
It achieves safe barrier properties of being fluorine-free, formaldehyde-free, and BPA-free, and improves the oil resistance, water resistance, heat resistance, and mechanical strength of the lunch box, meeting food contact safety and environmental protection requirements, without requiring modification of existing equipment.
Smart Images

Figure CN122325820A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of epoxy resin modified lunch box technology, specifically relating to an environmentally friendly lunch box material and its preparation process using lignin-based bio-based epoxy resin as a barrier coating and interlayer adhesive. Background Technology
[0002] Starch-based food containers are a mainstream environmentally friendly alternative to plastic containers due to their renewable and easily recyclable nature. Currently, commercially available starch-based food containers generally use oil-resistant coatings containing perfluorinated and polyfluoroalkyl compounds (PFAS) to achieve oil resistance, water resistance, and temperature resistance. Interlayer lamination often uses formaldehyde-containing urea-formaldehyde resins or phenolic resins, posing a risk of toxic substance migration. Some epoxy barrier coatings rely on bisphenol A (BPA) fossil-based raw materials, which do not meet food contact safety and carbon neutrality requirements. Furthermore, starch-based materials suffer from technical bottlenecks such as poor heat resistance and weak interfacial adhesion. The coating is prone to substrate deformation during high-temperature curing, limiting the application of high-performance barrier coatings.
[0003] Lignin, as an agricultural and forestry biomass and papermaking byproduct, is an ideal raw material for preparing bio-based epoxy resins. However, traditional lignin-based epoxy resins have problems such as low hydroxyl conversion rate, insufficient crosslinking density, high film brittleness, and poor resistance to media. They cannot be directly used as the main structure of lunch boxes, nor can they meet the requirements of low-temperature curing processes for starch-based substrates.
[0004] CN115850657A discloses a solventless method for preparing lignin-based biomass epoxy resin. This method involves extracting lignin from corn straw using bioethanol, followed by enzymatic hydrolysis and reaction with epichlorohydrin and a catalyst to prepare the lignin-based epoxy resin. However, the purity and homogeneity of the extracted lignin in this method still need improvement, affecting the performance of the final product.
[0005] CN117343282A discloses a method for preparing a flame-retardant lignin-based epoxy resin. This method increases the content of active hydroxyl groups on lignin through thermal degradation, introduces nitrogen, phosphorus, and silicon onto the lignin molecules using the Mannich reaction and chlorophosphosilane ester reaction, and then reacts with epichlorohydrin to obtain the flame-retardant lignin-based epoxy resin. However, the optimization of the reaction conditions in this method still needs further improvement, as it affects the yield and purity of the product.
[0006] Based on this, the present invention uses reduction-catalytic fractionation of lignin oligomers as raw materials to prepare high-performance BPA-free bio-based epoxy resin through deep epoxidation modification. This resin is used as a barrier coating and interlayer adhesive for starch lunch boxes. Surface pretreatment and silane coupling agents are used to enhance interfacial adhesion, and a low-temperature curing process is used to avoid substrate deformation. Without modifying existing starch lunch box production equipment, a safe barrier coating that is fluorine-free, formaldehyde-free, and BPA-free is achieved, while ensuring the lunch box's oil resistance, water resistance, heat resistance, and mechanical strength, thus overcoming the shortcomings of existing technologies. Summary of the Invention
[0007] 1. The problem to be solved The technical problem to be solved by this invention is to provide an environmentally friendly material for lunch boxes using lignin-based bio-based epoxy resin as a barrier coating and interlayer adhesive, and its preparation process. This solves the safety problems caused by the use of PFAS oil repellent, formaldehyde-based adhesives and BPA raw materials in existing starch lunch boxes, as well as the problems of low hydroxyl conversion rate, insufficient crosslinking density, high film brittleness and poor resistance to media in traditional lignin-based epoxy resins.
[0008] 2. Technical Solution To solve the above problems, the technical solution adopted by the present invention is as follows: This invention provides a method for preparing environmentally friendly materials for lunch boxes, comprising the following steps: Step S1: Preparation of lignin oligomers Using lignocellulose biomass as raw material, a mixture of a supported metal catalyst and an alcohol solvent is added to a high-pressure reactor. Hydrogen gas is introduced to a pressure of 25–35 bar, and the temperature is raised to 190–210 °C and maintained for 2.5–3.5 h to complete the reduction catalytic fractionation. After the reaction, the mixture is cooled and filtered to remove the catalyst, yielding lignin oil. The lignin oil is then extracted and separated using n-heptane to remove small molecule monomers, resulting in lignin oligomers with high hydroxyl content.
[0009] Step S2: Deep epoxidation synthesis of lignin-based epoxy resin A two-step epoxidation method was used to deeply epoxidize lignin oligomers to obtain deeply epoxidized lignin-based epoxy resins.
[0010] Step S3: Preparation of water-based epoxy coating liquid and adhesive Deeply epoxidized lignin-based epoxy resin was mixed with a food-grade nonionic emulsifier, and an aqueous epoxy emulsion was prepared by using a high-shear disperser. A food-grade curing agent was added, and the solid content was adjusted to 20-30 wt% to obtain an aqueous lignin-based epoxy system.
[0011] Step S4: Molding of corn starch-based lunch box substrate Starch-based lunchbox blanks are prepared by melt extrusion or hot pressing of food-grade corn starch. Step S5: Surface Pretreatment The surface of the starch-based food container substrate is subjected to plasma treatment or corona treatment with a power of 100-300W and a treatment time of 10-30s to increase the surface hydroxyl density and surface energy. Step S6: Coating and interlayer lamination process A water-based lignin-based epoxy system is uniformly coated on the inner side of a corn starch-based substrate and dried to form a barrier coating; or it is coated between two starch-based layers and hot-pressed to form an interlayer bond. Step S7: Low-temperature curing and molding The coated starch lunch box is sent into a hot air curing channel and cured at 80-110℃ for 2-5 minutes to allow the epoxy resin to fully cross-link and cure, while avoiding heat deformation of the starch substrate, thus obtaining the environmentally friendly material for the lunch box. The environmentally friendly material for the lunch box is formed on the inner side or between layers of the corn starch base substrate.
[0012] Explanation of Creative Mechanism The core innovation of this invention lies in adopting a "reduction catalytic fractionation + two-step deep epoxidation" technical route, and solving the technical problems of weak interfacial adhesion and thermal deformation of starch substrates through a "surface pretreatment + silane coupling agent + low-temperature curing" technical route. 1. Mechanism of Reduction Catalytic Fractionation (RCF): Under a hydrogen atmosphere and with a metal catalyst, the ether bonds (β-O-4, α-O-4, etc.) of the lignin-carbohydrate complex (LCC) in lignocellulose undergo selective cleavage, depolymerizing the lignin macromolecules into oligomers while avoiding condensation reactions. Compared with traditional lignin extraction methods (alkali lignin, enzymatic lignin), RCF lignin has a higher hydroxyl content (6.0–8.5 mmol / g) and a narrower molecular weight distribution (700–2000 g / mol), providing more reaction sites and better reaction uniformity for subsequent epoxidation reactions.
[0013] 2. Mechanism of Two-Step Deep Epoxidation: The first step of epoxidation, under mild conditions (50–70°C), utilizes the higher reactivity of phenolic hydroxyl groups compared to aliphatic hydroxyl groups, preferentially reacting the phenolic hydroxyl groups with epichlorohydrin to form aryl epoxy groups. This step avoids the ring-opening side reaction of epoxy groups caused by high temperatures. The second step of epoxidation uses potassium tert-butoxide to activate the remaining aliphatic hydroxyl groups, converting them into sodium alkoxide anions, significantly improving their nucleophilic reactivity, and then carrying out a deep epoxidation reaction with epichlorohydrin at 60–80°C. This step achieves highly efficient conversion of aliphatic hydroxyl groups, increasing the total functional group conversion rate to over 92%.
[0014] 3. High crosslinking density film formation mechanism: Deeply epoxidized lignin-based epoxy resins possess multiple epoxy functional groups (epoxy equivalent 230–240 g / eq), forming a highly crosslinked three-dimensional network structure during curing. Compared with traditional lignin-based epoxy resins, the crosslinking density is increased by 30%–50%, significantly improving the coating's density, barrier properties, and mechanical properties.
[0015] 4. Waterborne System Adaptation Mechanism: Lignin-based epoxy resin is emulsified through high-shear dispersion to form a waterborne emulsion with a narrow particle size distribution (average particle size 200–500 nm) and good stability. When used in conjunction with food-grade polyamide amine curing agents, it forms a waterborne epoxy system that can be directly applied to existing starch-based food container coating production lines without the need for organic solvents, thus meeting environmental protection requirements.
[0016] 5. Interfacial Bonding Mechanism of Starch Substrate: Corn starch substrate has a melt-molded structure with a smooth and dense surface, lacking the porous mechanical anchoring structure of paper-based materials. Coating adhesion primarily relies on interfacial hydrogen bonding. This invention enhances interfacial bonding through the following technical means: 5.1 Surface pretreatment: Plasma or corona treatment is used to introduce oxygen-containing functional groups (-OH, -C=O, etc.) on the surface of the starch substrate, thereby increasing the surface energy and reducing the water contact angle to below 50°, enhancing the wettability of the coating and the density of hydrogen bond binding sites.
[0017] 5.2 Silane Coupling Agent Reinforcement: The addition of silane coupling agents such as KH-550 and KH-560 allows their silane groups to hydrolyze and form Si-OC covalent bonds with the hydroxyl groups on the starch surface. The epoxy groups co-cur with the coating resin, forming a "chemical bridging" structure at the interface, significantly improving adhesion. Compared to traditional starch-based mechanical anchoring, the starch substrate achieves equal or better interfacial bonding strength through surface pretreatment and the synergistic effect of the coupling agent.
[0018] 6. Low-Temperature Curing Mechanism: Starch-based substrates have a low heat distortion temperature (approximately 60–80°C), and high-temperature curing will cause the substrate to soften and deform. This invention employs a low-temperature curing process (80–110°C) and ensures the curing effect through the following measures: 6.1 Preferred curing agent: Select aliphatic amines or modified polyamide amines with high activity to reduce the activation energy of the curing reaction and achieve rapid curing under low temperature conditions.
[0019] 6.2 Curing accelerator: Add a trace amount of phenolic resin or tertiary amine accelerator to accelerate the ring-opening reaction of epoxy groups and shorten the curing time.
[0020] 6.3 Formulation optimization: By adjusting the equivalent ratio of epoxy resin to curing agent and adding toughening agents, the crosslinking density and mechanical properties of the coating after low-temperature curing are ensured.
[0021] The weight-average molecular weight of the lignin oligomer is 700–2000 g / mol, and the total hydroxyl content is 6.0–8.5 mmol / g; the epoxy equivalent of the deeply epoxidized lignin-based epoxy resin is 230–240 g / eq, and the total functional group conversion rate is not less than 92%.
[0022] Preferably, in step S1, the lignocellulosic biomass is selected from one or more of hardwood sawdust, softwood chips, straw, and flax chips; the supported metal catalyst is selected from one or more of Ru / C, Pd / C, and Ni / SiO2-Al2O3.
[0023] Preferably, in step S1, the amount of catalyst used is 1 to 5 wt% of the biomass feedstock; the solvent is methanol or ethylene glycol, and the liquid-solid mass ratio is 8:1 to 12:1.
[0024] Preferably, in step S2, the two-step epoxidation method includes: Step 1: dispersing lignin oligomers in an anhydrous organic solvent, adding epoxy halogenated propane, and reacting at 50–70°C for 4–6 h under the action of an alkaline catalyst to convert phenolic hydroxyl groups into epoxy groups, obtaining a preliminary epoxidized lignin-based epoxy resin; Step 2: dissolving the preliminary epoxidized lignin-based epoxy resin in an anhydrous organic solvent under an inert atmosphere, activating the residual aliphatic hydroxyl groups with potassium tert-butoxide, and then adding epoxy halogenated propane and reacting at 65–85°C for 6–8 h to fully convert the aliphatic hydroxyl groups into epoxy groups, obtaining a deeply epoxidized lignin-based epoxy resin.
[0025] Potassium tert-butoxide (KOtBu), as a strongly basic alkoxide, is safer than potassium tert-butoxide when used under strictly anhydrous conditions. The reaction byproduct is tert-butanol, which can be recovered by vacuum distillation, eliminating the risk of hydrogen generation and making it suitable for industrial production.
[0026] Further, in the first step, the mass ratio of lignin oligomer to epoxy propane is 1:3 to 1:5; the alkaline catalyst is NaOH or KOH, and the amount used is 100% to 180% of the mass of lignin oligomer; in the second step, the amount of potassium tert-butoxide used is 25% to 85% of the mass of the initial epoxidized lignin-based epoxy resin.
[0027] Preferably, in step S3, the high-shear dispersion rotation speed is 8000–12000 r / min, and the dispersion time is 30–60 min; the epoxy group equivalent ratio of the curing agent to the epoxy resin is 0.9:1–1.1:1. The amount of silane coupling agent added is 0.5–2.0 wt% of the epoxy resin mass, and the silane coupling agent is selected from one or more of γ-aminopropyltriethoxysilane (KH-550), γ-glycidoxypropyltrimethoxysilane (KH-560), and γ-methacryloyloxypropyltrimethoxysilane (KH-570).
[0028] Further, in step S3, the food-grade nonionic emulsifier is a Tween series emulsifier, and the amount used is 3% to 8% of the mass of the lignin-based epoxy resin; it also includes the addition of food-grade leveling agent and toughening agent, with the addition amounts being 0.3% to 0.8% and 0.5% to 2.0%, respectively.
[0029] Preferably, in step S4, the temperature of the melt extrusion is 140–170°C, and the screw speed is 40–80 r / min; the temperature of the hot pressing is 150–180°C, the pressure is 5–15 MPa, and the time is 30–60 s.
[0030] Preferably, in step S5, the plasma treatment or corona treatment reduces the water contact angle of the substrate surface to below 50°.
[0031] Preferably, in step S6, the coating method is roller coating or spraying, and the wet film thickness is controlled to be 5-20 μm; the hot pressing temperature is 80-100℃, the pressure is 0.3-0.6 MPa, and the time is 15-40 s.
[0032] The present invention also provides an environmentally friendly material for lunch boxes, which is prepared by the above-mentioned method and includes a corn starch-based substrate and a lignin-based epoxy barrier coating coated on the inner surface of the corn starch-based substrate.
[0033] The lignin-based epoxy barrier coating is formed by curing lignin-based epoxy resin, which is prepared by the following method: using lignocellulose biomass as raw material, lignin oligomers are obtained by reduction catalytic fractionation, and then deep epoxidation modification is carried out by a two-step epoxidation method to obtain a deeply epoxidized lignin-based epoxy resin.
[0034] 3. Beneficial effects Compared with the prior art, the beneficial effects of the present invention are as follows: (1) Excellent food contact safety: This invention does not use PFAS oil repellent, formaldehyde-based adhesives, or bisphenol A raw materials. The lignin-based epoxy resin is derived from agricultural and forestry by-products, and after curing, there is no migration of toxic small molecules, which meets the safety requirements of GB 4806 food contact materials and poses no health or safety hazards. The starch base material is derived from corn starch, which is completely biodegradable and meets environmental protection requirements.
[0035] (2) Barrier performance meets the requirements of lunch box use: After curing, the coating is cross-linked and dense, with an oil resistance Kit value ≥10, which can withstand takeaway red oil and oily foods; the waterproof performance meets the standards, and there is no leakage, whitening and swelling when exposed to boiling water at 100℃ for a short period of time, which can meet the packaging requirements of hot food and soup.
[0036] (3) Mechanical and heat resistance properties are suitable for various application scenarios: The coating has a Young's modulus of 2180-2650 MPa, which is comparable to commercial epoxy. With the addition of a small amount of toughening agent, it can avoid bending and cracking. The thermal decomposition temperature is ≥320℃ and the heat resistance index is 158-175℃. It can withstand conventional microwave heating, boiling water contact and high temperature hot filling scenarios. The lunch box has high overall rigidity and is not easily deformed or damaged.
[0037] (4) Excellent interfacial bonding strength: Through the synergistic effect of surface pretreatment and silane coupling agent, the adhesion between starch substrate and coating reaches level 0 (excellent), which solves the technical problem of smooth surface and weak adhesion of starch substrate and achieves an interfacial bonding effect comparable to starch-based mechanical anchoring.
[0038] (5) Low-temperature curing process avoids substrate deformation: The low-temperature curing process of 80-110℃ is used, along with active curing agent and curing accelerator. While ensuring the cross-linking density of the coating, the problem of high-temperature softening and deformation of starch substrate is avoided. The process has strong adaptability and does not require modification of existing starch lunch box production equipment.
[0039] (6) Outstanding green sustainability: The raw materials are mainly industrial by-products lignin and corn starch. Each kilogram of lignin-based epoxy resin can reduce carbon emissions by 2.13 kg of CO2 equivalent. The coating is extremely thin, and the corn starch-based substrate can be normally recycled and regenerated, without the pressure of solid waste disposal, which is in line with the policy orientation of low-carbon environmental protection and recyclability.
[0040] (7) Overall performance is superior to traditional bio-based coatings: The resin crosslinking density is improved by deep epoxidation, which solves the problems of poor solubility, high film brittleness and insufficient resistance to media of traditional lignin materials. Under the premise of no fluorine and no formaldehyde, the performance of commercial fossil-based epoxy barrier systems is benchmarked. Attached Figure Description
[0041] Figure 1 This is a schematic cross-sectional view of the fluorine-free and formaldehyde-free lignin-based epoxy "barrier" starch lunchbox of the present invention. Figure 2 This is a schematic cross-sectional view of the fluorine-free and formaldehyde-free lignin-based epoxy "interlayer bonding" starch lunch box of the present invention. Figure 3 This is a flowchart illustrating the preparation process of the fluorine-free and formaldehyde-free lignin-based epoxy resin composite starch lunch box of the present invention. Detailed Implementation
[0042] The more detailed description of embodiments of the invention below is not intended to limit the scope of the claimed invention, but is merely illustrative and does not limit the description of the features and characteristics of the invention, in order to suggest the best mode for carrying out the invention and to enable those skilled in the art to practice the invention. However, it should be understood that various modifications and variations can be made without departing from the scope of the invention as defined by the appended claims. The detailed description should be considered illustrative only and not restrictive, and any such modifications and variations shall fall within the scope of the invention described herein. Furthermore, the background art is intended to illustrate the current state of research and development and significance of the technology, and is not intended to limit the invention or the scope of application of this application.
[0043] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains; the terminology used herein in the specification of this invention is for the purpose of describing particular embodiments only and is not intended to limit the invention. The invention is further described below with reference to specific embodiments.
[0044] Example
[0045] Example 1
[0046] like Figure 1 and Figure 3 As shown, this embodiment provides a method for preparing environmentally friendly materials for lunch boxes, including the following steps: Step S1: Preparation of lignin oligomers Using hardwood sawdust as raw material, 100g of hardwood sawdust (8% moisture content) was mixed with 3g of Ru / C catalyst (catalyst dosage was 3wt% of the biomass raw material mass) and 900g of methanol solvent (liquid-solid mass ratio 9:1) and added to a 2L high-pressure reactor. Hydrogen gas was introduced into the reactor to a pressure of 30 bar, the temperature was raised to 200℃, and the reaction was maintained at this temperature for 3 hours to complete the reduction catalytic fractionation (RCF). After the reaction was completed, the mixture was cooled to room temperature, filtered to remove the catalyst, and lignin oil was obtained. The lignin oil was extracted and separated using n-heptane (n-heptane to lignin oil volume ratio 3:1) to remove small molecule monomers. After rotary evaporation and concentration, a high-hydroxyl content lignin oligomer was obtained.
[0047] According to GPC analysis, the weight-average molecular weight of the lignin oligomers was 1350 g / mol, and the molecular weight distribution index was 1.85. According to ³¹P NMR analysis, the total hydroxyl content was 7.2 mmol / g, of which the phenolic hydroxyl content was 3.8 mmol / g and the aliphatic hydroxyl content was 3.4 mmol / g.
[0048] Step S2: Deep epoxidation synthesis of lignin-based epoxy resin High-functionality lignin-based epoxy resins were prepared using a two-step epoxidation method. Preliminary epoxidation: 20g of lignin oligomer was dispersed in 200mL of anhydrous tetrahydrofuran, and 80mL of epichlorohydrin (lignin oligomer to epichlorohydrin mass ratio 1:4) was added. The mixture was reacted at 60℃ for 5h under the action of 30g NaOH (alkaline catalyst, amount 150% of the lignin oligomer mass), preferentially converting the phenolic hydroxyl groups on the lignin oligomer into epoxy groups. After the reaction, the mixture was washed with water, solvent removed, and dried to obtain a preliminary epoxidized lignin-based epoxy resin (referred to as lignin-S resin, approximately 26-27g of which was obtained).
[0049] Deep epoxidation: The above lignin-S resin was dissolved in 150 mL of anhydrous tetrahydrofuran, and 9 g of potassium tert-butoxide (MW 112.2, approximately 0.080 mol, accounting for 33~35 wt% of the resin mass) was added. The mixture was activated under an anhydrous nitrogen atmosphere and stirred at 45 °C for 1.5 h to activate the residual aliphatic hydroxyl groups on the resin. Subsequently, 60 mL of epichlorohydrin was added again, and a deep epoxidation reaction was carried out at 75 °C for 7 h to fully convert the aliphatic hydroxyl groups into epoxy groups. The reaction solution was cooled to room temperature, filtered to remove the generated KCl salt, and the filtrate was neutralized, washed with water, and then subjected to vacuum distillation to remove THF and excess ECH, yielding a deeply epoxidized lignin-based epoxy resin (lignin-D resin).
[0050] The epoxy equivalent was determined by titration to be 235~240 g / eq; the total functional group conversion rate was calculated to be 91%~93% by ³¹P NMR.
[0051] Step S3: Preparation of water-based epoxy coating solution The prepared lignin-based epoxy resin was mixed with food-grade nonionic emulsifier Tween-80 (5 wt% of resin mass) and silane coupling agent KH-560 (1.0 wt% of epoxy resin mass). An aqueous epoxy emulsion was prepared using a high-shear disperser (10,000 r / min, 45 min dispersion time). A food-grade polyamide amine curing agent (epoxy group equivalent ratio of curing agent to epoxy resin was 1.0:1), 0.5 wt% food-grade leveling agent, 1.0 wt% toughening agent (carboxyl-terminated nitrile rubber), and 0.3 wt% curing accelerator (2,4,6-tris(dimethylaminomethyl)phenol) were added to adjust the solid content of the system to 25 wt%. After thorough stirring, an aqueous lignin-based epoxy system was obtained.
[0052] Step S4: Molding of corn starch-based lunch box substrate Food-grade corn starch (12% moisture content) was used as raw material and melt-extruded using a twin-screw extruder at an extrusion temperature of 160℃ and a screw speed of 60r / min to prepare a starch-based lunchbox preform with a thickness of 0.6mm.
[0053] Step S5: Surface Pretreatment The surface of a starch-based food container substrate was subjected to atmospheric pressure plasma treatment at a power of 200W for 20 seconds using air as the treatment gas. Testing showed that the water contact angle on the substrate surface was 72° before treatment, which decreased to 38° after treatment, indicating a significant increase in surface hydroxyl density.
[0054] Step S6: Coating process The starch-based food container substrate was placed on a conventional paper product coating production line. A water-based epoxy system was uniformly coated onto the inner side of the substrate using a roller coating method, with the wet film thickness controlled at 12μm and the dry film thickness at 4.0μm after drying.
[0055] Step S7: Low-temperature curing and molding The coated starch-coated lunchboxes are placed in a hot air curing channel and cured at 95°C for 3 minutes to allow the epoxy resin to fully cross-link and cure, resulting in an environmentally friendly material for the lunchboxes, forming a dense and continuous barrier film layer. After curing, the lunchboxes are cooled to room temperature to obtain a fluorine-free and formaldehyde-free lignin-based epoxy barrier starch-coated lunchbox.
[0056] Example 2 This embodiment provides a method for preparing an environmentally friendly material for lunch boxes. The difference from Embodiment 1 is that: in step S1, the weight-average molecular weight of the lignin oligomer is 800 g / mol, and the total hydroxyl content is 8.0 mmol / g; in step S3, the amount of silane coupling agent added is 0.5 wt%; in step S5, the plasma treatment power is 150 W, and the treatment time is 15 s; in step S6, the dry film thickness is 2.5 μm; and in step S7, the curing temperature is 80 °C, and the curing time is 5 min.
[0057] Example 3 This embodiment provides a method for preparing an environmentally friendly material for lunch boxes. The difference from Embodiment 1 is that: in step S1, the weight-average molecular weight of the lignin oligomer is 1800 g / mol, and the total hydroxyl content is 6.5 mmol / g; in step S3, the amount of silane coupling agent added is 1.5 wt%; in step S5, the plasma treatment power is 250 W, and the treatment time is 25 s; in step S6, the dry film thickness is 5.0 μm; and in step S7, the curing temperature is 110 °C, and the curing time is 2 min.
[0058] Example 4 This embodiment provides a method for preparing environmentally friendly materials for lunch boxes. The difference from Embodiment 1 is that: in step S1, straw is used as raw material, Pd / C is used as catalyst, the amount of catalyst is 2wt% of the biomass raw material, ethylene glycol is used as solvent, the liquid-solid mass ratio is 10:1, the reduction catalytic fractionation pressure is 28 bar, the temperature is 195℃, and the reaction time is 3.2 h; in step S3, KH-550 is used as silane coupling agent, and the amount added is 1.2wt%.
[0059] Example 5 This embodiment provides a method for preparing environmentally friendly materials for lunch boxes. The difference from Embodiment 1 is that: in step S2, the initial epoxidation temperature is 50°C and the reaction time is 6 hours; the deep epoxidation temperature is 60°C and the reaction time is 7 hours; the amount of potassium tert-butoxide is 65-70 wt% of the mass of lignin-S resin; in step S5, corona treatment is used instead of plasma treatment, the treatment power is 180W, and the treatment time is 18 seconds.
[0060] Example 6 This embodiment provides a method for preparing environmentally friendly materials for lunch boxes. The difference from Embodiment 1 is that in step S3, the high shear dispersion speed is 12000 r / min and the dispersion time is 30 min; the epoxy group equivalent ratio of the curing agent to the epoxy resin is 0.9:1; the solid content is 28 wt%; the silane coupling agent is KH-570 and the addition amount is 0.8 wt%.
[0061] Example 7 This embodiment provides a method for preparing environmentally friendly materials for lunch boxes, such as... Figure 2 As shown, the difference from Example 1 is that: in step S4, hot pressing molding is used instead of melt extrusion, the hot pressing temperature is 165℃, the pressure is 10MPa, and the time is 45s; in step S6, spray coating is used, and the wet film thickness is 15μm; it also includes an interlayer bonding process, in which a water-based epoxy system is uniformly coated between two starch-based layers (starch-based substrate 1 and starch-based substrate 2) as an adhesive, and the interlayer bonding is completed by hot pressing bonding (hot pressing temperature 90℃, pressure 0.4MPa, hot pressing time 25s).
[0062] Comparative Example Comparative Example 1 This comparative example provides a method for preparing an environmentally friendly material for lunch boxes. The difference from Example 1 is that in step S2, only preliminary epoxidation is performed, without deep epoxidation; the coating solution is directly prepared using lignin-S resin. The epoxy equivalent is 320 g / eq, and the total functional group conversion rate is 68%.
[0063] Comparative Example 2 This comparative example provides a method for preparing an environmentally friendly material for lunch boxes. The difference from Example 1 is that in step S1, alkali lignin (purchased from Sigma-Aldrich, weight-average molecular weight 4200 g / mol, total hydroxyl content 3.5 mmol / g) is used instead of the reduction-catalytic fractionation lignin oligomer.
[0064] Comparative Example 3 This comparative example provides a method for preparing an environmentally friendly material for lunch boxes. The difference from Example 1 is that in step S2, the deep epoxidation step does not use potassium tert-butoxide for activation; epichlorohydrin is added directly for the reaction. The epoxy equivalent is 285 g / eq, and the total functional group conversion rate is 78%.
[0065] Comparative Example 4 This comparative example provides a method for preparing an environmentally friendly material for lunch boxes. The difference from Example 1 is that in step S5, no surface pretreatment is performed, and the material is directly coated.
[0066] Comparative Example 5 This comparative example provides a method for preparing an environmentally friendly material for lunch boxes. The difference from Example 1 is that in step S3, no silane coupling agent is added, and only lignin-based epoxy resin, emulsifier, and curing agent are used to prepare the coating liquid.
[0067] Comparative Example 6 This comparative example provides a method for preparing an environmentally friendly material for lunch boxes. The difference from Example 1 is that in step S6, no lignin-based epoxy barrier coating is applied, and only a starch-based substrate is used.
[0068] Comparative Example 7 This comparative example provides a method for preparing an environmentally friendly material for lunch boxes. The difference from Example 1 is that in step S5, a commercial bisphenol A type epoxy coating (E-44 epoxy resin) is applied instead of a lignin-based epoxy coating.
[0069] Comparative Example 8 This comparative example provides a method for preparing an environmentally friendly material for lunch boxes. The difference from Example 1 is that in step S7, the curing temperature is 140℃, the curing time is 60s, and the starch substrate shows obvious deformation.
[0070] Performance testing The starch-based lunch boxes prepared in Examples 1-7 and Comparative Examples 1-8 were subjected to performance tests, and the relevant test methods are as follows: 1. Oil resistance performance: Kit value test was conducted in accordance with GB / T 22805.2-2008 "Determination of oil resistance of paper and paperboard - Part 2: Surface repulsion method".
[0071] 2. Waterproof performance: Water vapor transmission rate test was conducted according to GB / T 1037-2021 "Test method for water vapor transmission of plastic films and sheets"; Boiling water contact test: The coated surface was contacted with boiling water at 100℃ for 30 minutes, and the presence of leakage, whitening, or swelling was observed.
[0072] 3. Mechanical properties: The Young's modulus of the coating was tested in accordance with GB / T 1040.1-2018 "Determination of tensile properties of plastics".
[0073] 4. Heat resistance: The thermal decomposition temperature of the coating was tested using a thermogravimetric analyzer (TGA) (heating rate 10℃ / min, nitrogen atmosphere); the heat resistance index was tested according to GB / T 17391-1998 "Test Method for Thermal Stability of Polyethylene Pipes and Fittings".
[0074] 5. Food contact safety: Total migration was tested in accordance with GB 4806.7-2016 "National Food Safety Standard for Plastic Materials and Products for Food Contact"; GC-MS was used to detect the migration of PFAS, formaldehyde, and bisphenol A.
[0075] 6. Degree of curing: The degree of curing was calculated by measuring the change in the peak area of epoxy groups using the FTIR method.
[0076] Table 1 Barrier performance test results sample Kit value Water vapor transmission rate (g / m²·24h) Contact with boiling water at 100℃ for 30 minutes Example 1 11 95 No leakage, no whitening, no swelling Example 2 10 125 No leakage, slight whitening Example 3 12 78 No leakage, no whitening, no swelling Example 4 11 102 No leakage, no whitening, no swelling Example 5 11 92 No leakage, no whitening, no swelling Example 6 10 108 No leakage, no whitening, no swelling Example 7 12 85 No leakage, no whitening, no swelling Comparative Example 1 6 335 Severe leakage, whitening and swelling Comparative Example 2 7 295 Leakage, whitening Comparative Example 3 8 225 Slight leakage, whitening Comparative Example 4 9 185 Minor leakage Comparative Example 5 9 175 Minor leakage Comparative Example 6 2 920 Severe leakage Comparative Example 7 11 88 No leakage, no whitening, no swelling Comparative Example 8 8 180 Increased deformation and coating cracking Table 2 Mechanical Performance Test Results sample Young's modulus (MPa) Elongation at break (%) Coating adhesion (grade) Example 1 2420 3.0 Level 0 (Excellent) Example 2 2200 2.6 Level 0 (Excellent) Example 3 2580 3.3 Level 0 (Excellent) Example 4 2380 2.9 Level 0 (Excellent) Example 5 2450 3.1 Level 0 (Excellent) Example 6 2350 2.8 Level 0 (Excellent) Example 7 2520 3.2 Level 0 (Excellent) Comparative Example 1 1520 1.4 Level 3 (Poor) Comparative Example 2 1650 1.6 Level 3 (Poor) Comparative Example 3 1850 2.0 Level 2 (Intermediate) Comparative Example 4 2280 2.8 Level 1 (Good) Comparative Example 5 2320 2.7 Level 2 (Intermediate) Comparative Example 6 - - - Comparative Example 7 2500 2.9 Level 0 (Excellent) Comparative Example 8 1650 1.2 Level 4 (Poor) Table 3 Results of heat resistance test sample Thermal decomposition temperature (°C) Heat resistance index (°C) Appearance after heat treatment at 110℃ for 1 hour Example 1 332 165 No change Example 2 315 158 Slightly yellow Example 3 338 170 No change Example 4 325 162 No change Example 5 335 168 No change Example 6 328 164 No change Example 7 336 169 No change Comparative Example 1 272 135 Yellowing, brittle Comparative Example 2 282 140 Yellowing Comparative Example 3 295 145 Slightly yellow Comparative Example 4 320 158 No change Comparative Example 5 322 160 No change Comparative Example 7 - - Substrate softening and deformation Comparative Example 8 295 148 Severe deformation and cracking Table 4 Food contact safety test results sample Total migration (mg / dm²) PFAS migration (mg / kg) Formaldehyde migration (mg / kg) Bisphenol A migration (mg / kg) GB 4806.7 Conformity Assessment Example 1 3.8 Not detected Not detected Not detected qualified Example 2 5.2 Not detected Not detected Not detected qualified Example 3 3.2 Not detected Not detected Not detected qualified Example 4 4.2 Not detected Not detected Not detected qualified Example 5 3.5 Not detected Not detected Not detected qualified Example 6 4.0 Not detected Not detected Not detected qualified Example 7 3.0 Not detected Not detected Not detected qualified Comparative Example 1 9.5 Not detected Not detected Not detected qualified Comparative Example 2 13.5 Not detected Not detected Not detected qualified Comparative Example 3 8.0 Not detected Not detected Not detected qualified Comparative Example 4 4.5 Not detected Not detected Not detected qualified Comparative Example 5 4.8 Not detected Not detected Not detected qualified Comparative Example 6 2.5 Not detected Not detected Not detected qualified Comparative Example 7 4.0 Not detected Not detected 0.15 Unqualified Comparative Example 8 8.2 Not detected Not detected Not detected qualified In summary, regarding barrier performance, the Kit values of Examples 1-7 are all ≥10, the water vapor transmission rate is all <125 g / m²·24h, and there is no leakage, whitening, or swelling after 30 minutes of contact with boiling water at 100℃, meeting the requirements for food containers. Comparative Example 1 (preliminary epoxidation only) has a Kit value of only 6, but a water vapor transmission rate as high as 320 g / m²·24h, indicating that deep epoxidation is crucial for barrier performance. Comparative Example 2 (alkali lignin) and Comparative Example 3 (without potassium tert-butoxide activation) also have poor performance, proving that the selection of raw materials and processes has a significant impact. Comparative Example 4 (no surface pretreatment) and Comparative Example 5 (no silane coupling agent) show a slight decrease in performance, indicating that surface pretreatment and coupling agents contribute to barrier performance.
[0077] From a mechanical property perspective, the Young's modulus of Examples 1-7 ranged from 2180 to 2650 MPa, comparable to Comparative Example 7 (commercial BPA epoxy), with elongation at break of 2.6% to 3.3%, and coating adhesion of all examples was grade 0 (excellent). The Young's modulus of Comparative Examples 1-3 was significantly lower (1520-1850 MPa), indicating that deep epoxidation improved the crosslinking density and mechanical strength. The adhesion of Comparative Example 4 (without surface pretreatment) and Comparative Example 5 (without silane coupling agent) was grade 1 and grade 2, respectively, demonstrating that surface pretreatment and coupling agents significantly affect interfacial adhesion.
[0078] In terms of heat resistance, Examples 1-7 have a thermal decomposition temperature ≥315℃ and a heat resistance index ≥158℃, meeting the requirements for microwave heating and high-temperature hot filling. Comparative Examples 1-3 have lower thermal decomposition temperatures and heat resistance indices, indicating that the functional group conversion rate directly affects heat resistance. The deformation of the starch substrate in Comparative Example 8 after curing at 140℃ demonstrates the necessity of a low-temperature curing process.
[0079] From a food contact safety perspective, PFAS, formaldehyde, and bisphenol A were not detected in Examples 1-7 and Comparative Examples 1-6, and the total migration amount was <10 mg / dm² (GB 4806.7 limit), meeting food safety requirements. Comparative Example 7 showed a bisphenol A migration amount of 0.15 mg / kg, which did not meet the requirements of GB 4806.7, demonstrating the necessity of the BPA-free design of this invention.
[0080] From a process compatibility perspective, all embodiments employ an aqueous system and a low-temperature curing process. The coating and curing process parameters are compatible with traditional paper product coating processes, and no special equipment such as high pressure or high temperature is used, proving that this invention is suitable for continuous industrial production. Low-temperature curing (80–110°C) avoids the thermal deformation problem of the starch substrate while ensuring the crosslinking density and performance of the coating.
[0081] It is evident that the environmentally friendly material for lunch boxes creatively prepared by this invention has significant advantages in barrier properties, mechanical properties, heat resistance, food contact safety, and process adaptability, and has broad application prospects.
[0082] The present invention has been described in detail above with reference to specific exemplary embodiments. However, it should be understood that various modifications and variations can be made without departing from the scope of the invention as defined by the appended claims. The detailed description should be considered illustrative only and not restrictive, and any such modifications and variations shall fall within the scope of the invention described herein. Furthermore, the background art is intended to illustrate the current state of development and significance of the technology and is not intended to limit the present invention or the scope of application of the present application.
[0083] More specifically, although exemplary embodiments of the invention have been described herein, the invention is not limited to these embodiments, but includes any and all embodiments modified, omitted, such as combinations between various embodiments, adaptive changes, and / or substitutions, as would be apparent to those skilled in the art from the foregoing detailed description. The limitations in the claims are to be interpreted broadly as used in the language of the claims and are not limited to the examples described in the foregoing detailed description or during the implementation of this application, which should be considered non-exclusive. Any step listed in any method or process claim may be performed in any order and is not limited to the order set forth in the claims. Therefore, the scope of the invention should be determined solely by the appended claims and their legal equivalents, and not by the description and examples given above.
[0084] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. In case of conflict, the definitions in this specification shall prevail. When flow rate, power, refractive index, time, or other values or parameters are expressed as ranges, preferred ranges, or a series of upper and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pair of any upper or preferred value with any lower or preferred value, regardless of whether such range is disclosed individually. For example, the range 1-50 should be understood to include any number, combination of numbers, or subrange selected from 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, or 50, as well as all decimal values between the integers mentioned above, such as 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, and 1.9. Regarding subranges, specifically consider "nested subranges" extending from any endpoint of the range. For example, nested sub-ranges of the exemplary range 1-50 may include 1-10, 1-20, 1-30 and 1-40 in one direction, or 50-40, 50-30, 50-20 and 50-10 in another direction.
Claims
1. A method for preparing an environmentally friendly material for lunch boxes, characterized in that, Includes the following steps: Step S1: Preparation of lignin oligomers Using lignocellulose biomass as raw material, a mixture of a supported metal catalyst and an alcohol solvent is added to a high-pressure reactor. Hydrogen gas is introduced to a pressure of 25–35 bar, and the temperature is raised to 190–210 °C and maintained for 2.5–3.5 h to complete the reduction catalytic fractionation. After the reaction, the mixture is cooled and filtered to remove the catalyst, yielding lignin oil. The lignin oil is then extracted and separated using n-heptane to remove small molecule monomers, yielding lignin oligomers with high hydroxyl content. The weight-average molecular weight of the lignin oligomers is 700–2000 g / mol, and the total hydroxyl content is 6.0–8.5 mmol / g. Step S2: Deep epoxidation synthesis of lignin-based epoxy resin A two-step epoxidation method was used to deeply epoxidize lignin oligomers to obtain deeply epoxidized lignin-based epoxy resins; the epoxy equivalent of the deeply epoxidized lignin-based epoxy resins was 230-240 g / eq, and the total functional group conversion rate was not less than 90%; Step S3: Preparation of water-based epoxy coating liquid and adhesive Deeply epoxidized lignin-based epoxy resin is mixed with food-grade nonionic emulsifier and silane coupling agent, and an aqueous epoxy emulsion is prepared by high shear dispersion. Food-grade curing agent is added and the solid content is adjusted to 20-30 wt% to obtain an aqueous lignin-based epoxy system. Step S4: Molding of corn starch-based lunch box substrate Starch-based lunchbox blanks are prepared by melt extrusion or hot pressing of food-grade corn starch. Step S5: Surface Pretreatment The surface of the starch-based food container substrate is subjected to plasma treatment or corona treatment with a power of 100-300W and a treatment time of 10-30s to increase the surface hydroxyl density and surface energy. Step S6: Coating and interlayer lamination process A water-based lignin-based epoxy system is uniformly coated on the inner side of a corn starch-based substrate and dried to form a barrier coating; or it is coated between two starch-based layers and hot-pressed to form an interlayer bond. Step S7: Low-temperature curing and molding The coated starch lunch box is sent into a hot air curing channel and cured at 80-110℃ for 2-5 minutes to allow the epoxy resin to fully cross-link and cure, while avoiding heat deformation of the starch substrate, thus obtaining the environmentally friendly material for the lunch box. The environmentally friendly material for the lunch box is formed on the inner side or between layers of the corn starch base substrate.
2. The preparation method according to claim 1, characterized in that, In step S1, the lignocellulosic biomass is selected from one or more of hardwood sawdust, softwood chips, straw, and flax chips; the supported metal catalyst is selected from one or more of Ru / C, Pd / C, and Ni / SiO2-Al2O3.
3. The preparation method according to claim 1, characterized in that, In step S1, the amount of catalyst used is 1 to 5 wt% of the biomass feedstock; the solvent is methanol or ethylene glycol, and the liquid-solid mass ratio is 8:1 to 12:
1.
4. The preparation method according to claim 1, characterized in that, In step S2, the two-step epoxidation method includes: Step 1: Disperse lignin oligomers in an anhydrous organic solvent, add epoxy halopropane, and react at 50-70℃ for 4-6 hours under the action of an alkaline catalyst to convert phenolic hydroxyl groups into epoxy groups, thereby obtaining a preliminary epoxidized lignin-based epoxy resin. Step 2: Dissolve the preliminary epoxidized lignin-based epoxy resin in an anhydrous organic solvent under an inert atmosphere, activate the residual aliphatic hydroxyl groups with potassium tert-butoxide, and then add epoxy halopropane and react at 65-85℃ for 6-8 hours to fully convert the aliphatic hydroxyl groups into epoxy groups, thereby obtaining the deeply epoxidized lignin-based epoxy resin.
5. The preparation method according to claim 4, characterized in that, In the first step, the mass ratio of lignin oligomer to epoxide halopropane is 1:3 to 1:5; the alkaline catalyst is NaOH or KOH, and the amount used is 100% to 180% of the mass of lignin oligomer; in the second step, the amount of potassium tert-butoxide used is 25% to 85% of the mass of the initial epoxidized lignin-based epoxy resin.
6. The preparation method according to claim 1, characterized in that, In step S3, the high-shear dispersion rotation speed is 8000-12000 r / min, and the dispersion time is 30-60 min; the epoxy group equivalent ratio of the curing agent to the epoxy resin is 0.9:1-1.1:1; the amount of silane coupling agent added is 0.5-2.0 wt% of the epoxy resin mass, and the silane coupling agent is selected from one or more of γ-aminopropyltriethoxysilane (KH-550), γ-glycidoxypropyltrimethoxysilane (KH-560), and γ-methacryloyloxypropyltrimethoxysilane (KH-570).
7. The preparation method according to claim 1, characterized in that, In step S3, the food-grade nonionic emulsifier is a Tween series emulsifier, and the amount used is 3% to 8% of the mass of the lignin-based epoxy resin; it also includes the addition of food-grade leveling agent and toughening agent, with the addition amounts being 0.3% to 0.8% and 0.5% to 2.0%, respectively.
8. The preparation method according to claim 1, characterized in that, In step S4, the temperature of the melt extrusion is 140-170℃, and the screw speed is 40-80 r / min; the temperature of the hot pressing is 150-180℃, the pressure is 5-15 MPa, and the time is 30-60 s. In step S5, the plasma treatment or corona treatment reduces the water contact angle on the substrate surface to below 50°.
9. The preparation method according to claim 1, characterized in that, In step S6, the coating method is roller coating or spraying, and the wet film thickness is controlled to be 5-20 μm; the hot pressing temperature is 80-100℃, the pressure is 0.3-0.6 MPa, and the time is 15-40 s.
10. An environmentally friendly material for lunch boxes, characterized in that, It is prepared by the preparation method according to any one of claims 1-9.
Citation Information
Patent Citations
Preparation method and application of flame-retardant lignin-based epoxy resin
CN117343282A
